1992
DOI: 10.1128/mcb.12.9.3689
|View full text |Cite
|
Sign up to set email alerts
|

Increased gene-specific repair of cisplatin interstrand cross-links in cisplatin-resistant human ovarian cancer cell lines.

Abstract: We have studied several aspects of DNA damage formation and repair in human ovarian cancer cell lines which have become resistant to cisplatin through continued exposure to the anticancer drug. The Cells in culture were treated with cisplatin, and the two main DNA lesions formed, intrastrand adducts and interstrand cross-links, were quantitated before and after repair incubation. This quantitation was done for total genomic lesions and at the level of individual genes. In the overall genome, the initial freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
85
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(90 citation statements)
references
References 21 publications
5
85
0
Order By: Relevance
“…This is in accordance with a previous report proposing that ERCC-1 is more important for the repair of MMC induced crosslinks than UV induced damage (32). Furthermore, it was shown that overexpression of the human ERCC-1 gene may inhibit a pathway specific to the repair of ICL (33), and that acquired cellular resistance to cisplatin may be associated with increased gene-specific repair efficiency of interstrand crosslinks (34).…”
Section: Discussionsupporting
confidence: 80%
“…This is in accordance with a previous report proposing that ERCC-1 is more important for the repair of MMC induced crosslinks than UV induced damage (32). Furthermore, it was shown that overexpression of the human ERCC-1 gene may inhibit a pathway specific to the repair of ICL (33), and that acquired cellular resistance to cisplatin may be associated with increased gene-specific repair efficiency of interstrand crosslinks (34).…”
Section: Discussionsupporting
confidence: 80%
“…They are multifaceted and complex, and can include the involvement of membrane-associated e ux pumps, the up-regulation of cellular detoxifying thiols, enhanced DNA repair activity and the inhibition of apoptotic pathways (Ishikawa et al, 1994;Andrews et al, 1985;Lai et al, 1988Lai et al, , 1989Chu, 1994;Chu and Chang, 1990;Zhen et al, 1992;Miyake et al, 1998;Citro et al, 1998). In many malignancies, drug resistance is acquired through prolonged and repeated exposure to a chemotherapeutic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Repair studies at the nucleotide level are also particularly important in the investigation of anti-cancer drugs. For example Zhen et al (35), using Southern blotting, have found differences in the gene specific repair of cisplatin interstrand, but not intrastrand, crosslinks which seemed to correlate with the degree of resistance to the drug. Further studies on nucleotide-specific lesions will help to identify molecules capable of creating lesions which are resistant to repair.…”
Section: Discussionmentioning
confidence: 99%